2005
DOI: 10.3200/socp.145.2.127-140
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure in Romantic Relationships and Friendships Among American and Japanese College Students

Abstract: The author examined whether the level of self-disclosure would differ across four types of relationships--passionate love relationships, companionate love relationships, same-sex friendships, and cross-sex friendships--and across cultures: American culture and Japanese culture. Participants were 145 college students (64 Americans and 81 Japanese). The results supported three hypotheses: (a) Japanese students scored lower in self-disclosure than American students, regardless of relationship types, (b) self-disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 24 publications
4
50
1
3
Order By: Relevance
“…Since individuals are viewed as representatives of the collective unit, nondisclosure may prevent loss of face (Liao, Rounds, & Klein, 2005;Sue, Zane, & Young, 1994). An interdependent sense of self involves regarding personal attributes as secondary to those of the group (Kito, 2005) and extending one's sense of responsibility beyond immediate family. This may involve prioritizing others' potential reactions to their disclosure over personal consequences and internal experiences.…”
Section: Av and Disclosure Of Abusementioning
confidence: 99%
“…Since individuals are viewed as representatives of the collective unit, nondisclosure may prevent loss of face (Liao, Rounds, & Klein, 2005;Sue, Zane, & Young, 1994). An interdependent sense of self involves regarding personal attributes as secondary to those of the group (Kito, 2005) and extending one's sense of responsibility beyond immediate family. This may involve prioritizing others' potential reactions to their disclosure over personal consequences and internal experiences.…”
Section: Av and Disclosure Of Abusementioning
confidence: 99%
“…Perhaps Iranian undergraduate and graduate students experience FIL at a similar rate as those from other cultures, but are less comfortable endorsing and discussing this experience. Past literature (e.g., Kito, 2005) has shown that culture influences self-disclosure about romantic relationships. Or perhaps Iranians understand, define, and evaluate FIL differently, holding a higher bar for what constitutes a FIL experience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dion and Dion (1993) found that love is experienced more strongly in individualistic cultures (compared with collectivistic cultures). Others have found that those from Western cultures (compared with those from Eastern cultures) are more emotionally expressive (Kito, 2005;Tsai & Levenson, 1997) and report emotional experiences (including passion) more strongly (Gao, 2001;Markus & Kitayama, 1991).…”
Section: Isolationmentioning
confidence: 99%
“…The first variable is the realization that various racial groups have interpersonal patterns (e.g., self-disclosure, expression of feelings, physical expressions of affection, expression of vulnerability, etc.) that are deeply rooted in the social, historical, political and economic experiences of their racial groups (Kito 2005). These interpersonal patterns may develop as a result of these aforementioned experiences and shape how people perceive themselves, their racial identity and their perceptions of members of other racial groups (Kao and Vaquera 2006;Kito 2005;McKinney 2006).…”
Section: Relational Variables In Cross-racial Friendshipsmentioning
confidence: 98%